2016
DOI: 10.1155/2016/4063137
|View full text |Cite
|
Sign up to set email alerts
|

Four-Strand Core Suture Improves Flexor Tendon Repair Compared to Two-Strand Technique in a Rabbit Model

Abstract: Introduction. This study was designed to investigate the influence of the amount of suture material on the formation of peritendinous adhesions of intrasynovial flexor tendon repairs. Materials and Methods. In 14 rabbits, the flexor tendons of the third and the fourth digit of the right hind leg were cut and repaired using a 2- or 4-strand core suture technique. The repaired tendons were harvested after three and eight weeks. The range of motion of the affected toes was measured and the tendons were processed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…1 Other studies suggest that additional epitendinous suture may lead to greater bulk at the repair site along with an increased inflammatory response increasing the risk of adhesion formation. 13,14 However, these findings are not consistent among all studies. 15 Our clinical data are in line with studies supporting epitendinous suture, as greater IP motion implies fewer adhesions.…”
Section: Discussionmentioning
confidence: 81%
“…1 Other studies suggest that additional epitendinous suture may lead to greater bulk at the repair site along with an increased inflammatory response increasing the risk of adhesion formation. 13,14 However, these findings are not consistent among all studies. 15 Our clinical data are in line with studies supporting epitendinous suture, as greater IP motion implies fewer adhesions.…”
Section: Discussionmentioning
confidence: 81%
“…Besides, FiberWire (Arthrex, Naples, FL) was found to be a superior suture material in a study [ 30 ]. In addition, four-strand core sutures lead to less gapping but caused more inflammatory response within the tendon [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with our hypothesis, results of this study show that increasing the number of suture strands crossing the repair and increasing the level of suture purchase from the transection site are positively correlated with repair site strength while reducing the occurrence of gap formation in a cadaveric gastrocnemius model. While multiple sources in both the veterinary and human literature report variations of multi-strand repairs, 19,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] the authors of the current study sought to modify existing patterns to Fig. 4 Box and whisker plot showing failure loads of tenorrhaphies repaired with a two-strand (Group 1), four-strand (Group 2) and sixstrand locking repair (Group 3) using 2-0 USP polypropylene.…”
Section: Discussionmentioning
confidence: 99%
“…18,[24][25][26][27] Within the human literature, it has been demonstrated that increasing the number of strands traversing the repair site increases the overall strength of tendon repair. 19,[28][29][30][31][32][33][34][35][36][37][38] In the veterinary literature, the 3LP has been demonstrated to be biomechanically superior, compared with the LL pattern, 39 likely as it relies on multiple divergent passes and utilizes six strands that cross the repair site. 25,39 The LL has previously been demonstrated to be inferior to 3LP regarding loads tolerable prior to failure and ultimate tensile strength.…”
Section: Introductionmentioning
confidence: 99%